AN INTEGRATED SERVICE EXCELLENCE MODEL FOR MILITARY TEST AND EVALUATION FACILITIES - De Coning, Gerhard; Van der Waldt, Gerrit (Scientia Militaria - South African Journal of Military Studies, 2011)
The purpose of this article is to introduce an Integrated Service Excellence Model (ISEM) for empowering the leadership core of the capital-intensive military test and evaluation facilities to provide strategic military test and evaluation services and to continuously improve service excellence by ensuring that all activities necessary to design, develop and implement a test and evaluation service are effective and efficient. In order to develop the ISEM, various management tools and productivity and quality models were identified and tested through an empirical study conducted amongst the various test and evaluation facilities’ leadership core. Solutions to financial, human resource and environmental challenges as well as quality standards were built into the ISEM. Governance principles and leadership perceptions and recommendations further contributed to the development of the ISEM.